Comparative Analysis of Primary and Secondary Metabolites in the Peel of Eight Blood Orange Varieties - Melgarejo, Pablo; Ballesta-de los Santos, Manuel; Martínez-Nicolás, Juan J.; Melián Navarro, Amparo; Ruiz-Canales, Antonio; Forner-Giner, María A.; Legua, Pilar (MDPI, 2023)
The global cultivation of blood oranges is experiencing an increase due to their remarkable nutritional properties. Blood orange by-products, especially the peel, have a high concentration of bioactive compounds with exceptional antioxidant potential, making them an ideal choice for incorporation into various food products. This study aimed to determine the morphological parameters and primary and secondary metabolite content of peel of eight blood orange varieties using 1H NMR and HPLC-ESI-DAD-MSn. “Tarocco Meli” had the highest weight (367.83 g), caliber (94.13 mm and 88.87 mm), peel thickness (6.73 mm), and peel weight (155.0 g). “Tarocco Rosso”, “Sanguinelli”, and “Tarocco Gallo” had the highest levels of total amino acids (25.57 g kg−1 DW), total organic acids (29.99 g kg−1 DW), and total sugars (68.56 g 100 g−1 DW), respectively. The peel of “Moro” had significantly higher concentrations of total anthocyanins, hydroxycinnamic acids, and flavones (650.67, 263.33, and 449.85 mg kg−1, respectively) compared to the other varieties. In conclusion, “Tarocco Meli” had the most interesting values for morphological parameters, “Tarocco Rosso”, “Sanguinelli”, and “Tarocco Gallo” for primary metabolites, and “Moro” for secondary metabolites. With the increasing interest in utilizing co-products, these findings could be useful in developing functional food products that meet consumer demands for healthier and more sustainable food choices.